Meningkatkan hasil belajar matematika dengan menggunakan metode role playing pada pembelajaran aritmetika sosial - Ati Suciati; Ricky Yuliardi; Zuli Nuraeni (JUMLAHKU: Jurnal Matematika Ilmiah STKIP Muhammadiyah Kuningan, 2018)
Students low ability on mathematics in elementary school can caused students low motivation on mathematics in Junior high school. Because of students low motivation on learning mathematics. The student achievement in mathematics be come lower. Weekness of student participation in social arithmetic subject caused many Students have lower value from Minimum KKM which applied at school. The problem of study in this research are : How the Students Participation after applied role playing method on social arithmetic subject in class VII C SMPN 1 Karangkancana. How the students learning outcomes after applied role playingmethod on social Arithmetic Subject in class VII C SMPN 1 Karangkancana. Role playing method is learning method where students group playing roles which there is story questions while other students group doing observation. The Procedure of this PTK Study divided into two Cycle. Every Cycle Consist of twice meeting, twice meeting to delivering subject and once meeting to do evaluation. Based on the result of this research, it can be seen on cycle I and cycle II in student assessment activity that psychomotor aspect gained average value 69 with good enough criteria on cycle I while on cycle II gained average value 84 with good criteria. Whereas in cognitive activity that measure students level Comprehension Concept especially on evaluation activity, it found that student average value on cycle I is 65,76 with KKM level 61,57 after that on cycle II found that students average value is 79,23 with KKM level achieved 92,30 % and student participation on cycle I less have an active roles. It can be seen on student psychomotor aspect gained average value 69 whereas on cycle II student participation has improved with achieved average value in student psychomotor is 84. We can concluded that learning with role playing method can improves student active role and student achievement on mathenatics learning activity. In student class VII SMPN 1 Krangkancan